PENGARUH PROFESIONALISME, ETIKA, INDEPENDENSI, PENGALAMAN DAN PENGETAHUAN MENDETEKSI KEKELIRUAN TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS (Studi Empiris pada Auditor Badan Pengawasan Keuangan dan Pembangunan (BPKP) Perwakilan Provinsi Riau) - Selvy De Balqis; Raja Adri Satriawan Surya; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to identify and analyze the influence of Profesionalism, Ethic, Independency, Working Experiences, and Auditor’s Knowledge of Error on Judgement of Materiality Level. This research used primary data from questioner filled by functional auditors of Perwakilan BPKP Provinsi Riau. This study used random sampling method and used multiple linear regression as the analysis instrument, by using SPSS (Statistical Product and Service Solution) ver. 21 software. Four hypothesis shows there are influences beetween Profesionalism, Ethic, Independency, Working Experiences, and Auditor’s Knowledge of Error on Judgement on Materiality level. The influnce of Profesionalism, Ethic, Independency, Working Experiences, and Auditor’s Knowledge of Error are 45,6 %, while the remaining 54,4 % is influenced by other variables.Keywords : Materiality level, Profesionalism, Ethic and Independency